Tidally‐averaged flows in the interior Sacramento–San Joaquin River Delta: Trends and change attribution. Issue 2 (4th December 2018) - Hutton, Paul H.; Chen, Limin; Rath, John S.; Roy, Sujoy B.
Abstract: The hydrology of the San Francisco Bay‐Delta estuary (the Delta) has been significantly modified over the past 150 years to serve a variety of human needs for water supply and food production, albeit with adverse ecological impacts. These adverse impacts, in concert with evolving societal values, have motivated change in the estuary's water management to promote ecosystem restoration goals while continuing to support human uses. Understanding historical flow patterns, as well as the environmental functions provided by these flow patterns, is critical to restoration planning. Building upon previous work on outflow trends from the Delta to San Francisco Bay, this paper evaluates historical trends in key interior Delta flows spanning nine decades (1922–2016) and presents an attribution of these trends to various anthropogenic drivers. We reconstructed historical time series records at four key locations in the interior of the Delta; these time series represent tidally‐averaged flows that are intensively managed and are of great importance to the beneficial uses of water in the region. We derived several scenario‐based flow time series at these same four locations to assist in attributing change to a variety of drivers, including reservoir and export pumping operations, in‐Delta barrier and gate operations, and upstream water diversions. Flow changes were measured relative to 1920‐level land use and water management conditions. We find the four interior Delta locations to have distinct seasonal flow trends and, in general, unique responses to various drivers of change. Our work highlights the complex nature of historical flow changes in a highly‐managed estuarine ecosystem, and the types of modifications that would be necessary to reverse these changes.